Influence of clonazepam on cortical epileptic afterdischarges in rats - Kubová, H; Makal, V; Minová, M; Vanková, S; Mares, P (Archives internationales de pharmacodynamie et de therapie, 1990)
Epileptic afterdischarges were induced by low frequency stimulation of the sensorimotor cortex in rats with implanted electrodes. Stimulations were repeated 4 times with 10 min intervals. Stimulation was always accompanied by clonic jerkings of the forepaws and frequently also by rearing and falling of the animals even in cases when no afterdischarge followed. Afterdischarges formed by a spike-and-wave rhythm prevailed, but a transition to spikes superimposed on delta waves ("slow waves superimposed with spikes") as well as a "slow waves superimposed with spikes" type since the very beginning of afterdischarges were recorded. Spike-and-wave afterdischarges were accompanied by the same motor pattern as stimulation, i.e., by minimal clonic seizures. During the "slow waves superimposed with spikes" type of afterdischarges, the rats sat motionless; wet dog shakes appeared towards the end. Mixed types of afterdischarges were accompanied by both motor patterns closely correlated to the actual EEG pattern. Clonazepam (0.02, 0.1 or 1 mg/kg, i.p.) was injected 5 min after the first afterdischarge. The second afterdischarge was shortened in a dose-dependent manner. The shortening was also observed in the third and fourth afterdischarge. Both pure afterdischarge types (spike-and-wave and "slow waves superimposed with spikes") could be induced after clonazepam, whereas a mixed type of afterdischarges was abolished. Motor pattern accompanying stimulation was attenuated but never abolished by clonazepam, whereas the same clonic seizures during spike-and-wave afterdischarges were blocked by the highest dose of clonazepam. Dissociation of EEG and motor epileptic phenomena suggests a preferential action of clonazepam on generalization of epileptic activity.
Keywords: Animals; elektrická stimulace; Electric Stimulation; Epilepsy; Electrodes, Implanted; inbrední kmeny potkanů; klonazepam; Electrophysiology; somatosenzorické korové centrum; somatosenzorické evokované potenciály; Evoked Potentials, Somatosensory; Rats, Inbred Strains; Somatosensory Cortex; Clonazepam; epilepsie; Male; implantované elektrody; krysa rodu Rattus; elektrofyziologie; mozková kůra; Cerebral Cortex; zvířata; mužské pohlaví; elektroencefalografie; Rats; Electroencephalography